Formulation, Development and Evaluation of Etoricoxib Nanosize Microemulsion Based Gel for Topical Drug Delivery - Fonseca, Vania Rachael; Bhide, Prashant Jivaji; Joshi, Madhusudan Purushottam (Indian Journal of Pharmaceutical Education and Research, 2019)
Introduction: Etoricoxib is a poorly water-soluble oral NSAID and is associated with a number of complications such as bleeding, ulcers and dyspepsia but these can be overcome by delivering the drug topically. Objectives: Microemulgel for the topical delivery of etoricoxib was formulated to increase its solubility and thus improve the skin permeability. Methods: The solubility of etoricoxib was studied in various oils, surfactants and cosurfactants. Pseudo-ternary phase diagrams were constructed by varying the surfactant to cosurfactant (Smix) ratio. Microemulsions with different compositions were formulated and optimized. Selected o/w microemulsions contained 1% etoricoxib and were evaluated for pH, rheology, drug content, particle size and in vitro drug release. Optimized microemulsion was incorporated in 1% Carbopol® 934 and was evaluated for rheological properties, spreadability, in vitro permeation, skin irritation and stability. Results: Capryol™ 90, Tween 80 and Transcutol® P exhibited the highest solubility. Maximum microemulsion region was observed when the Smix ratio was 3:1. The average particle size of the optimized microemulsion was 37.61 nm, zeta potential was -2.88 mV and permeability of the drug from the microemulsion was 66.8% after 8 h. The prepared gel showed 57.8% drug release after 8 hr. Skin irritation studies indicated that the optimized formulation was safe for topical application. Stability studies indicated that the formulation remained unaffected at accelerated storage conditions. Conclusion: Results indicated that the micro-emulgel has potential for sustained action of drug release and may act as a promising tool to enhancepercutaneous delivery of etoricoxib.
Keywords: Etoricoxib; Microemulsion; Topical gel; in vitro release; Particle size; Skin; irritation